Survey data harmonization in the social sciences - Słomczyński, Kazimierz M.; Tomescu-Dubrow, Irina; Wolf, Christof; Jenkins, J. Craig 1948- (Hoboken, New Jersey Wiley, 2023)
"Survey data harmonization combines survey methods, statistical techniques, and substantive theories to create datasets that facilitate comparative research. Both data producers and secondary users engage in harmonization to achieve or strengthen the comparability of answers from respondents surveyed in different populations or over time"--
Includes bibliographical references and index.
Keywords: Social sciences -- Data processing; Social surveys -- Methodology